Exclusive Breastfeeding Support and Barriers for Working Mothers in Sukoharjo, Indonesia Judging from Theory of Planned Behavior and Social Cognitive Theory - Ichsan, Burhanuddin; Candrasari, Anika; Maulana, Faiz; Anam, Zahra Hafizha Fitria (MAGNA MEDIKA Berkala Ilmiah Kedokteran dan Kesehatan, 2024)
Background:  The World Health Organization (WHO) recommends exclusive breastfeeding for six months. Many intervention programs to increase the coverage of exclusive breastfeeding have been carried out, but the coverage of exclusive breastfeeding has not increased significantly. A systematic review analyzed several factors that influence exclusive breastfeeding in developing countries. Mother's occupation was found to be the most frequently mentioned obstacle.Objective: These studies show that the working status of the mother is something that greatly influences the success of exclusive breastfeeding.Methods: This research is a qualitative phenomenological study to see the support and barriers to exclusive breastfeeding for mothers who work in Sukoharjo.Results: The theme found in this study is the support and inhibition of exclusive breastfeeding for working mothers as seen from the Theory of Planned Behavior and Social Cognitive Theory. The obstacles are: 1) incorrect knowledge about exclusive breastfeeding, 2) barriers from some health workers/institutions, 3) families do not support exclusive breastfeeding, 4) there is no regulation on exclusive breastfeeding in the workplace, 5) the workplace does not yet have a special place for pumping and storing breast milk, 6) does not have a role model, 7) breast milk is reduced by working, 8) already has the intention to mix with formula milk, 9) low self-efficacy, and 10) barriers from the baby's internal factors. The supports are: 1) support from health workers/institutions, 2) the workplace provides a special room for pumping and/or storing breast milk, 3) there is an opportunity for pumping breast milk in the workplace, 4) peer support, 5) there is a high expectation of health. good, 6) intention to exclusively breastfeed, 7) good self-efficacy, 8) family support, 9) leave from work and light workload, 10) skills in breastfeeding, 11) no obstacles from the leadership, and 12) smooth mother's milk.Conclusion: This shows that SCT and TPB can be used as a theory to see the variables that influence the practice of exclusive breastfeeding. There is one finding that cannot be directly included in the SCT and/or TPB constructs, namely: skills in providing breast milk.